SEMIOTIC ANALYSIS ON WEIGHT LOSS PRODUCT ADVERTISEMENTS - Rosmaidar Rosmaidar; Tita Ratna Wulandari; Galiansa Galiansa (Global Expert: Jurnal Bahasa dan Sastra, 2017)
The objectives of this study were to find outthe types of semiotic signs, the verbal and visual meanings of these signs, and the relationship among verbal and visual signs used in weight loss product ads. Qualitative method with descriptive approach was used in this study. 10 weight loss product ads were used in this study. There are icons, indexes, and symbols found in this study. There are 10 icons (100%), 7 indexes (70%), and 4 symbols (40%). Peirce’s theory was used in finding the types of semiotics in this study, and Saussure’s theory was used in finding the verbal and visual meanings as well as its relationship among them. The result of the study shows that the verbal and visual signs are used to create clear meanings and both of them have strong relationship in delivering messages of the products.Key words : Semiotic, Weight Loss Product Advertisements, and Verbal and Visual Signs.